Transaction cost implication of private branding and empirical evidence - Chen, Shih‐Fen S. (Strategic Management Journal, 2009)
Branding and transaction cost economics represent two research streams that rarely cross paths in the literature. In this study, I explore the transaction cost implication of private branding, a practice whereby products supplied by unaffiliated manufacturers are sold under private brands owned by retailers. The main thesis is that private branding can preempt a special case of asset specificity called brand specificity, where retailers also invest in the marketing of an outsourced product, but subsequent reputation effects (positive or negative) are specific to the manufacturer who brands the product. Retailers, thus, will not be fully motivated to optimize their investment in product marketing unless they take over the branding right. With potential barriers to private branding being controlled, data obtained from a national chain reveal that the retailer deploys its marketing resources according to the branding status of a product, implying that private branding can deflect the transaction cost of solving the brand specificity problem. The results offer new theoretical insights into branding and transaction cost analysis. This efficiency‐based approach to private branding also provides practitioners with useful guidelines for crafting a branding strategy that will facilitate cooperation between manufacturers and retailers. Copyright © 2009 John Wiley & Sons, Ltd.